2012
DOI: 10.1063/1.4767141
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of a patterned and buried molecular layer by coherent acoustic phonon spectroscopy

Abstract: Influence of crystallographic orientation and anisotropy on Kapitza conductance via classical molecular dynamics simulations J. Appl. Phys. 112, 093515 (2012) Pulsed terahertz radiation due to coherent phonon-polariton excitation in 110 ZnTe crystal J. Appl. Phys. 112, 093110 (2012) Dynamical thermal conductivity of bulk semiconductor crystals J. Appl. Phys. 112, 083515 (2012) Influences of lattice vibration and electron transition on thermal emissivity of Nd3+ doped LaMgAl11O19 hexaaluminates for metall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…We obtain a readily usable analytic expression assuming that the gold mode frequency is only slightly influenced by the molecular layer. This assumption is corroborated by measurements on patterned APTES layer systems 15 where we observed negligible frequency shifts with or without APTES layer between the gold film and the substrate. The details regarding the theoretical calculations are given in the Theory section.…”
Section: Resultssupporting
confidence: 83%
“…We obtain a readily usable analytic expression assuming that the gold mode frequency is only slightly influenced by the molecular layer. This assumption is corroborated by measurements on patterned APTES layer systems 15 where we observed negligible frequency shifts with or without APTES layer between the gold film and the substrate. The details regarding the theoretical calculations are given in the Theory section.…”
Section: Resultssupporting
confidence: 83%
“…Sub-nanometer thick interfacial layers separating thin films from the substrate can influence both the decay time of the thin film vibration [18] and propagation of the coherent acoustic pulses [19]. Later it was demonstrated thatthe quantitative evaluation of the thickness of broad interfacial layers [20][21][22][23][24] and the rigidity of thin interfacial bonds [2, 25-29] can be obtained. Here, we study interfacial adhesion as well as damping behaviorin two-layer Al/Si-membranes.…”
mentioning
confidence: 99%
“…Picosecond ultrasonics is a technique, developed in the mid-1980s, in which ultrashort laser pulses are used to generate and detect acoustic waves with very short wavelength, typically in a nanometer range [1]. Established applications of the method include the determination of elastic parameters [2][3][4][5][6][7][8][9], acoustic damping properties [10][11][12][13][14][15], structural properties [16][17][18][19], interface adhesion and coupling [20][21][22][23] and imaging of embedded layers [24][25][26][27][28][29]. Ultrafast acoustic dynamics were studied in metals [6,21,[30][31][32][33][34][35], semiconductors [10,[36][37][38][39], dielectric materials [11,14,16,40] and polymers [41]…”
Section: Introductionmentioning
confidence: 99%